Optimal spatial adaptation to inhomogeneous smoothness: an approach based on kernel estimates with variable bandwidth selectors - Lepskii, Oleg V.; Mammen, Enno; Spokojnyj, Vladimir G. (The annals of statistics, 1997)
A new variable bandwidth selector for kernel estimation is proposed. The application of this bandwidth selector leads to kernel estimates that achieve optimal rates of convergence over Besov classes. This implies that the procedure adapts to spatially inhomogeneous smoothness. In particular, the estimates share optimality properties with wavelet estimates based on thresholding of empirical wavelet coefficients.
First available in Project Euclid: 20 November 2003
Gesehen am 15.02.2018